Genomic analysis of two all-stage stripe rust resistance genes in the Vavilov wheat landrace AGG40807WHEA1 - Raghvendra Sharma; Chunhong Chen; Peng Zhang; Hemlata Bharti; Venu Kumaran Vikas; Michael Norman; Katherine Dibley; Adnan Riaz; Tim Hewitt; Sami Hoxha; Kerrie Forrest; Evans Lagudah; et al. (Theoretical and Applied Genetics, 2025)
Key message Comparative genomic analysis of two all-stage stripe rust resistance loci from Vavilov wheat landrace accession, AGG40807WHEA1, using Chinese Spring and 10 + hexaploid wheat genomes and validation of closely linked KASP markers. Abstract The ongoing occurrence and spread of wheat stripe rust, caused by the fungal pathogen Puccinia striiformis f. sp. tritici , threatens the global food security. Cultivation of varieties with effective sources of resistance is often followed by the appearance of virulent pathotypes at various times after their introduction. This requires an ongoing search for new sources. Tests of 296 accessions from the Vavilov wheat landrace collection identified numerous lines with broadly effective all-stage stripe rust resistance. Genetic analysis of one of these accessions (Australian Grains Genebank number AGG40807WHEA1) identified two all-stage resistance genes, temporarily named YrV1 and YrV2 . The YRV1 and YRV2 loci were mapped to 3.48–3.98 and 730.2–731.2 Mb intervals in the short arm of chromosome 3B and the long arm of chromosome 7B, respectively. A comparative genomic analysis of the YRV1 locus in the Chinese Spring and the 10 + wheat pangenome databases revealed genomic rearrangements and lack of sequences encoding a nucleotide-binding and leucine-rich repeat (NLR) domain protein. Sequences belonging to NLR -like genes were present in the YRV2 region. Kompetitive allele-specific PCR (KASP) markers designed from SNPs IWB71814 and IWB69562 , located at 0.4 cM and 0.5 cM distal to YrV1 and YrV2 , respectively, were validated for marker-assisted selection using 123 hexaploid and 15 tetraploid wheat and 14 triticale cultivars. YrV1 and YrV2 genes are potentially valuable resources, and use of the closely linked molecular markers will expedite their deployment in breeding.